An epidemiological study to assess the true incidence and prevalence of rheumatic heart disease and acute rheumatic fever in New Caledonian school children. (20th May 2016) - Corsenac, Philippe; Heenan, Rachel C; Roth, Adam; Rouchon, Bernard; Guillot, Nina; Hoy, Damian
Abstract : Aim: To provide in New Caledonian school children (i) the prevalence of rheumatic heart disease (RHD) detected by annual screening program using new World Heart Federation diagnostic criteria; (ii) the point prevalence of acute rheumatic fever (ARF); and (iii) to investigate socio‐demographic risk factors associated with RHD. Methods: This study linked data from national ARF/RHD programs by combining ARF incidence data from the register with RHD prevalence data from echocardiographic screening data for a single age year of the population for overall point prevalence ARF/RHD rates. For the analysis, cases of echocardiographic detection of RHD are presumed to be synonymous with undiagnosed ARF. All results were weighted to minimise the bias introduced from absent pupils of each annual screening program. Incidence and prevalence were age‐standardised to the WHO World Standard Population. Each 2013 cumulative prevalence of definite and borderline RHD was studied using a multivariate logistic regression adjusted for socio‐demographic factors. Results: The overall age‐standardised incidence of clinical and undiagnosed ARF (i.e. echocardiographic‐detected RHD) was combined as point prevalence and estimated to be 99/10 000 cases in 2012 and 114/10 000 cases in 2013. This included 40/10 000 prevalent cases of asymptomatic RHD detected by screening each year. Being Melanesian, OR 23.2 (95% CI: 3.4–157.3), or Polynesian, OR 21.5 (95% CI: 2.9–157.7), was associated with a higher prevalence of having definite RHD compared with being Caucasian. Being a girl was associated with a higher risk of having borderline RHD, OR 1.9 (95% CI: 1.03–3.3). Conclusion: Without echocardiographic screening, ARF/RHD burden is substantially underestimated.